Incorporating rivest-shamir-adleman algorithm and advanced encryption standard in payment gateway system - Veronica Veronica; Raymond Sunardi Oetama; Arief Ramadhan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
The rapid development of technology has led to various advancements, including the ability to conduct online payments through applications. Companies providing digital transaction payment services require a payment gateway system as an intermediary for online transactions. The system acts as an intermediary between merchants with digital wallets and banks, involving the company, merchants, and banks in its development. The system includes essential features like bill payment, user credit card verification, and transaction checking, customized to meet the specific requirements of merchants and adhere to security standards. In this study, we incorporated the rivest-shamir-adleman (RSA) algorithm and advanced encryption standard (AES) to ensure the security of a payment gateway system. We adopt the agile methodology in the development process of the system. We test the acceptance of the system to the user, and we also test the performance of the system. The results of this research show that the system can be accepted by the user, fulfill the user's needs, can be executed well, and performs adequately in handling multiple transactions concurrently. The outcome of this study can serve as valuable input for the company in building its own system, providing insights into algorithm implementation techniques and the system workflow.